SYNTHETIC SEISMIC RECORDS FROM HETEROGENEOUS MEDIA USING THE RAY TRACING METHOD - Ahmad Yusuf; Djoko Rubyanto; Suprajitno Munadi (Scientific Contributions Oil and Gas, 1995)
Ray tracing method can be used to generate artificial seismic records from a heterogeneous medium which depend on the structure and stratification of the geologic model. The ray tracing method is a forward modelling process which is able to visualize the seismic wave propagation and its corresponding seismic record from different geologic models, so that the dominant parameters which control the model can be understood.